Application of Microbial-Based Inoculants for Reducing N2O Emissions From Soil Under Two Different Ammonium Nitrate–Based Fertilizers. Issue 9 (September 2016) - Calvo, Pamela; Watts, Dexter B.; Kloepper, Joseph W.; Torbert, H. Allen
Abstract : Abstract: Considerable effort is being made within the scientific community to identify mechanisms to reduce nitrous oxide (N2 O) emissions from agricultural soils. The objective of this study was to test the hypothesis that microbial-based inoculants known to promote root growth and nutrient uptake will reduce N2 O emissions in the presence of ammonium nitrate–based nitrogen fertilizers under controlled conditions. The microbial-based treatments evaluated were SoilBuilder (SB), a metabolite extract of SoilBuilder (SoilBuilder product filtered [SBF]), and a mixture of four strains of plant growth–promoting Bacillus species (BM). Experiments included an unfertilized control and two different nitrogen fertilizers: ammonium nitrate (AN) and calcium ammonium nitrate (CAN). Nitrous oxide and carbon dioxide (CO2 ) emissions were measured from soil incubations using gas chromatography. After 29 days of incubation, cumulative N2 O emissions were reduced 81%, 67%, and 50% for the SBF, SB, and BM treatments, respectively, in soils fertilized with CAN. In the unfertilized treatment, cumulative N2 O emissions with SBF were significantly reduced by 92%, compared with the uninoculated control. Emissions from the AN treatment were generally lower than those from CAN. Microbial-based treatments increased N2 O emissions when applied with AN, with SBF resulting in the greatest flux. No differences in total CO2 emissions were observed among treatments when AN was applied. Microbial-based treatments increased CO2 emissions from soils fertilized with CAN and from the unfertilized control, indicating a possible increase in microbial activity. Overall, the results demonstrated that microbial-based inoculants can impact (reduce or increase) N2 O emissions from soil. This response is highly dependent on the fertilizer type and microbial-based product applied. Future research is planned to determine the mechanisms involved in reducing N2 O emissions when these microbial inoculants are added to the system.